The management of post-infectious hydrocephalus in people living with HIV: a prospective observational study - Lekoloane, Reneiloe M (Division of General Surgery, 2024)
Post-infectious hydrocephalus (PIH) in people living with HIV (PLHIV) is a common complication presenting to neurosurgeons in South Africa, but there is limited evidence to guide management of these patients. Objectives The study aimed to prospectively document the in-hospital management and 12 month neurological and survival outcomes of PIH in people living with HIV (PLHIV). Methods The study included a consecutive series of 23 people living with HIV (PLHIV) presenting to a tertiary hospital in 2018 with a diagnosis of post infectious hydrocephalus who were followed up for a 12-month period. Baseline demographics, HIV data, and Glasgow Coma Score, aetiology of post infectious hydrocephalus and treatment modality were documented. Survival outcomes and neurological function (modified Rankin Scale) were assessed. The cohort was divided into non-randomised treatment groups, surgical (ventriculoperitoneal shunts/ external ventricular drain) and medical (lumbar spinal taps) based on institutional practice. Results PIH aetiologies were noted as tuberculous in 78.3% (n=18) and cryptococcal in 21.7% (n=5). Overall survival at discharge was 69,9% (n=16) and 47.8% (n=11) at 12 months follow up. Functional outcomes expressed as mRS, resembled the survival data, showing favourable outcomes at 12 months within the survival group. Linear regression analysis showed that the cohort had an unchanged mRS during the 12-month period (p=0.008) Conclusion The limited data from this study suggest that a proactive therapeutic approach to PIH should be offered to virologically suppressed individuals. A tiered treatment algorithm is proposed to guide the treatment of these patients. Further studies using this treatment algorithm could provide a more accurate representation of outcomes in this population.